NIPPONOTROPHON MAKASSARENSIS, A NEW RECENTLY DREDGED MURICACEAN SPECIES OF STRANGE GENERIC AFFINITIES (GASTROPODA: MURICIDAE) - Houart, Roland (Marine Research in Indonesia, 1984)
A murieid, dredged by the French-Indonesian "CORINDON" expedition (1980) in the Strait of Makassar was recently brought to my attention. After carefully checking in the literatures, it appears to be new, but one problem was remaining unresolved: its classification in an appropriate genus.